MITOCHONDRIAL DNA D-LOOP SEQUENCE BASED PHYLOGENY OF PAKISTANI BUFFALO (BUBALUS BUBALIS) - M. Y. Zahoor1; M. Imran; Z. Zaheer; T. Mahmood; I. Rashid; K. Ashraf; M. Iqbal; W. Shehzad (Journal of Animal and Plant Sciences, 2016)
It is uncertain whether domestication of Pakistani river buffalo (Bubalus bubalis) occurred together with or independent of other buffalo species/subtypes. Sequence analysis of the mtDNA D-loop region of Pakistani buffaloes revealed a total of 24 polymorphic sites and 4 haplotypes. These haplotypes were compared in phylogenetic trees with 347 additional mtDNA D-loop sequences already reported for river and swamp buffaloes. All phylogenetic trees revealed two major clades: the river buffalo and the swamp buffalo clade. Among the river buffalo clade were present a number of subclades representing distinct matrilineal and geographic origins. These findings indicate that multiple domestication events have occurred in river buffalo, leading to independent expansion of some maternal lineages with minimum introgression from wild populations.
Keywords: Bubalus bubalis; domestication; genetic diversity; water buffalo; Pakistan